ANALYSIS OF EXPERIENTIAL AND EMOTIONAL MARKETING EFFECTS ON THE DECISION TO ENTER IN UNIVERSTAS AMIKOM YOGYAKARTA - Amrullah, Yusuf Amri (Program Studi Manajemen, 2021)
This study analyzes the influence of Experiential Marketing and Emotional Marketing on The Decision to Enter at Universitas AMIKOM Yogyakarta. The purpose of this study was to examine the effect of using Experiential Marketing and Emotional Marketing on The Decision to Enter at Universitas AMIKOM Yogyakarta. This research is vital to be used by companies or agencies that will conduct marketing. Respondents in this study were new students of Universitas AMIKOM Yogyakarta force 2018/2019 with at least one faculty represented by 1 study program, the questionnaire to distributed amounted to 200 questionnaires. Data analysis in this research uses validity test, reliability test and classic assumption test. The results of data processing using SPSS, the results shown are Experiential Marketing and Emotional Marketing influence on The Decision Enter.